Impact of Human Resources Management Strategies on Job Satisfaction of the Employees of the Social Security Corporation in Jordan (Global Journal of Management and Business Research, 2017)
Abstract not found
Keywords: human resources management strategies; job satisfaction; social security corporation; jordan